Asian-Pacific leadership: Implications for foreign economic policy of Japan and the US - Ulrich Hiemenz (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
In the 1980s, the Western Pacific hemisphere ranging from Japan and the PR China to Australia and New Zealand has remained the growth pole of the world economy. Real per capita incomes of East and Southeast Asian developing economies grew even faster in this decade than in the 1970s [World Bank, 1990: Table 1.3] despite major disturbances in their global environment such as the world-wide recession in the early 1980s, increasing protectionism in the EC and the US, large exchange rate fluctuations, high and volatile real interest rates, and commodity price shocks. The integration into the international division of labour in manufactures was a driving force behind the favourable economic performance of Asian-Pacific economies in the 1980s. This is reflected in the growing importance of manufactures and in particular capital goods in their export basket. In 1988, about 44 per cent of all developing countries' exports originated from the Asian-Pacific region [World Bank, 1990: Table 14], and Asian NIEs and Near NIEs participated overproportionately in the expansion of highly income elastic intra-industry trade with capital goods [GATT, 1989: Table 4].
Keywords: 330; Außenwirtschaftspolitik; Japan; USA